Lipidomic changes in the liver of beagle dogs associated with Toxocara canis infection - Li, Hao-Yu; Zou, Yang; Elsheikha, Hany M.; Xu, Yue; Cai, Lang; Xie, Shi-Chen; Zhu, Xing-Quan; Zheng, Wen-Bin (Frontiers in Cellular and Infection Microbiology, 2022)
In this study, lipid alterations in Beagle dog’s liver caused by Toxocara canis infection were investigated by using liquid chromatography with tandem mass spectrometry at 12 hours post infection (hpi), 24 hpi and 36 days post infection (dpi). A total of 6 categories and 42 subclasses of lipids were identified, including 173, 64 and 116 differentially abundant lipid species at 12 hpi, 24 hpi and 36 dpi, respectively. Many of the identified lysophospholipids, such as lysophosphatidylglycerol, lysophosphatidyiserine and lysophosphatidylcholine, seem to contribute to the migration and development of T. canis at the early infection stage. Pathway analysis revealed significant alterations of several lipid metabolism pathways, such as B cell receptor signaling pathway, NF-kappa B signaling pathway and C-type lectin receptor signaling pathway at 12 hpi and 24 hpi. Our findings provide the first detailed insight into how T. canis infection causes substantial changes in the composition and abundance of hepatic lipid metabolites with relevance to pathophysiology of toxocariasis in Beagle dogs.